2019
DOI: 10.1021/acsomega.9b00101
|View full text |Cite
|
Sign up to set email alerts
|

New Set of Multicomponent Crystals as Efficient Heterogeneous Catalysts for the Synthesis of Cyclic Carbonates

Abstract: Three new multicomponent crystals 1a–1c of Zn(II), Mn(II), and Co(II), respectively, were synthesized by the reaction of 2,6-bis(hydroxymethyl)pyridine, the respective metal salts, and sodium benzoate in a 1:1:2 ratio. One component of these multicomponent crystals 1a–1c is the dicationic 2,6-bis(hydroxymethyl)pyridine metal complex and the other component is the dianionic tetrabenzoate complex of the same metal. The complexes were fully characterized by single-cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Cocrystallization has evolved as a strategy to develop novel solid forms of materials, particularly pharmaceuticals, 1−7 agrochemicals, 8,9 and other specialty chemicals, 10,11 to improve their physicochemical properties such as solubility, dissolution rate, hygroscopicity, stability, and mechanical properties. In this process, a multicomponent crystal, known as a cocrystal, is obtained by molecular mixing of two components, each of which are solid under ambient conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocrystallization has evolved as a strategy to develop novel solid forms of materials, particularly pharmaceuticals, 1−7 agrochemicals, 8,9 and other specialty chemicals, 10,11 to improve their physicochemical properties such as solubility, dissolution rate, hygroscopicity, stability, and mechanical properties. In this process, a multicomponent crystal, known as a cocrystal, is obtained by molecular mixing of two components, each of which are solid under ambient conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cocrystallization has evolved as a strategy to develop novel solid forms of materials, particularly pharmaceuticals, agrochemicals, , and other specialty chemicals, , to improve their physicochemical properties such as solubility, dissolution rate, hygroscopicity, stability, and mechanical properties. In this process, a multicomponent crystal, known as a cocrystal, is obtained by molecular mixing of two components, each of which are solid under ambient conditions. , Understanding the thermodynamic properties of a cocrystal is essential to provide insights into its production, stability, and utilization. While multiple methodologies have been reported for screening and manufacturing of cocrystals, the preparation of cocrystals by slurrying the components in a solvent is still the most widely followed method from the early development to the late phase of production. , Obtaining solubility data during development studies is routine.…”
Section: Introductionmentioning
confidence: 99%
“…13 C­{1H} NMR (100 MHz,DMSO- d 6 , 27 °C) δ­(ppm) = 158.0 (C = O), 73.49 (O–CH), 70.44 (O–CH2), 18.94 (CH3) (Figures S32 and 33). Analytical data were in accordance with the literature. , …”
Section: Methodsmentioning
confidence: 52%
“…The catalytic cycloaddition reaction of the epoxides 2 and 3 to the corresponding cyclic carbonates 4 and 5 as shown in Scheme 2 was tried at 10 bar pressure of CO 2 and 80 o C in a 100 mL reactor with one-dimensional coordination polymers 1a and 1b as catalysts. In the previously reported studies of conversion of CO 2 to cyclic carbonates, it was observed that the reaction proceeds with the addition of the cocatalyst 37,39,48,49 tetrabutylammonium bromide along with the metal-based catalysts. In recent years, ionic liquid-based heterogeneous catalytic systems have been developed, which usually perform the catalytic reaction at higher temperature and pressure 5052 but the reaction yield is found to be very high and with higher turnover numbers.…”
Section: Resultsmentioning
confidence: 99%